Social Movement, Action and Change: The Influence of Women's Movements on City Government in Mumbai and London - Jim Barry, Trudie Honour and Sneha Palnitkar (Gender, Work and Organization. Vol. 11 No. 2 March 2004, 2004)
This article reports on a research investigation into gender and local government in Mumbai in India and London in England. In both these cities female representation at the political level stands at around one third, achieved in London slowly in recent years and in Mumbai more rapidly through the adoption of a quota, or seat reservation system, implemented in 1992. In considering the experience of the women concerned it is argued that their presence and aspirations have been influenced through the networks of their respective women's movements, operating through civil society and the local state. In considering the ways in which they organize and manage the duties of office and their gendered identities, as well as in their focus on the most disadvantaged in their communities and in their dealings with others, the part played by social movements in influencing change is examined.